Effects of alcohol on the symptoms of gouty arthritis and taxonomic structure of gut microbiota in C57BL/6 mice - Feng, Yu; Sun, Haihui; Zhu, Ruilou; Tao, Jianxing; Su, Rui; Sun, Yundong; Wang, Dawei (Frontiers in Microbiology, 2023)
Gout is an acute arthritis caused by the elevated levels of serum uric acid (UA), and its prevalence has been rapidly increasing. Alcohol abuse could lead to a series of health problems. Multiple pieces of evidence suggest that alcohol intake affects the development and progression of gout, while the gut microbiota plays an important role in the development of gout and the long-term alcohol consumption could affect the stability of the gut microbiota. This study aimed to explore the effects of alcohol intake at different concentrations on gouty arthritis based on the gut microbiota. We investigated the effects of different concentrations of alcohol on gouty arthritis in mouse models of acute gouty arthritis established by injection of monosodium urate (MSU) crystals into C57BL/6 mice. The results indicated that the high-alcohol consumption not only exacerbated joint swelling and pain, increased the levels of UA, tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6), but also showed dramatic effects on the composition and structure of the gut microbiota in gouty mice. Two key microorganisms, Parasutterella and Alistipes, could aggravate gout symptoms through lipopolysaccharide biosynthesis, riboflavin metabolism, phenylalanine metabolism, and arginine and proline metabolisms. In conclusion, our study suggested that high-concentrations of alcohol altered the gut microbiota structure in gouty mice induced by MSU crystals, which could exacerbate gouty symptoms by enhancing pro-inflammatory pathways.